Pengaruh Frekuesi Pendinginan yang Berbeda Terhadap Daya Tetas Telur Itik Persilangan Cihateup Alabio - Rukmiasih, Rukmiasih; Afnan, R.; Darajah, F. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Increasing of duck rearing as a meat producer requires an increase in duck population to fulfill the demand.  The objective of this research was to analyze the proper chilling frequency to increase duck egg hatchability from cihateup alabio cross breeds.  Chilling frequencies used in this study were once, twice, and three times.  One time chilling was done in the afternoon (12.00-13.00).  Two times chilling was done in the morning (06.00-07.00) and in the evening (17.00-18.00).  Three times chilling was done in the morning (06.00-07.00), in the afternoon (12.00-13.00), and in the evening (17.00-18.00).  Materials used in the research were digital thermometer, 491 eggs from Balitnak Ciawi, KMnO4, Na2CO3, 40% formalin, and chlorin.  The result showed a high fertility on duck egg from Cihateup Alabio cross breeds (>75% on average) with 4 : 16 (male : female) sex ratio.  All of the chilling frequencies had no significant effect on egg hatchability from Cihateup Alabio cross breeds.